A fluorescent AND logic gate based on a ferrocene-naphthalimide-piperazine format responsive to acidity and oxidizability. (October 2018) - Spiteri, Jake C.; Johnson, Alex D.; Denisov, Sergey A.; Jonusauskas, Gediminas; McClenaghan, Nathan D.; Magri, David C.
Abstract: A novel fluorescent molecular logic gate1 is demonstrated as a two-input AND logic gate for the detection of acidity and oxidizability. Designed according to an electron-donor–spacer–fluorophore–spacer–receptor ' format, the modules are represented by ferrocene as the electron donor, 1, 8-naphthalimide as the fluorophore and piperazine as the proton receptor. In the presence of elevated concentrations of H + and Fe 3+, the molecule switches 'on' emitting at λ max = 530 nm with Φ f = 0.060 at 10 −4 M H + and 50 μM Fe 3+ . The H + binding and apparent Fe 3+ binding constants determined by fluorimetric titrations in 1:1 ( v/v ) methanol/water are log β H+ = 8.1 and log β Fe3+ = 4.7. Modulation of the fluorescence output results from controlling competing photoinduced electron transfer (PET) at the ferrocene end and internal charge transfer (ICT) at the piperazine end. Time-resolved fluorescence spectroscopy reveals a single fluorescent lifetime of 5.8 ns, while from absorption transient spectroscopy a remarkable fast decay signal <2 ps is observed. Comparison is made with methylpiperazine2 and piperazine fluorescent pH indicator3 as model compounds. Graphical abstract: Highlights: A fluorescent AND logic gate responses to acidity and oxidizability. A green fluorescence is observed at high proton and ferric ion levels. Techniques include steady-state and time-resolved fluorescence spectroscopy.